Pencarian Rute Terpendek dari Kampung Duri Kosambi Menuju Sekolah Tinggi Ilmu Komputer Cipta Karya Informatika Jakarta Timur Menggunakan Algoritma A* (A-Star) - Ahluna, Faza; Arinal, Veri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Cipta Karya Informatika Computer Science College (STIKOM CKI) is one of the educational institutions that focuses on computer education. Marked by the issuance of a permit on September 5, 2002, in the form of a Decree of the Minister of National Education No.: 204 / D / O / 2002 which legally has two departments of Informatics Engineering and Information Systems that have implemented a competency-based curriculum. The campus is on Jalan Radin Inten II Duren Sawit, East Jakarta. One of the important educational institutions for the local community and students who live around it. However, accessibility to the campus can be a challenge for individuals who come from the Kampung Duri Kosambi area, right in Duri Kosambi Village, Cengkareng District, West Jakarta. To determine the closest route, it has now been widely applied in various navigation applications such as the Global Positioning System, Google Maps, A * Star is one of the optimal route search algorithms. Optimal means that the route produced is the best and most complete route, the algorithm can achieve the expected goal. In addition, the purpose of this study is to provide information about the location of the STIKOM CKI campus for the nearest route so that it can help users to choose the fastest route to get to the location and at the same time provide information on the nearest route based on the results of the A*Star algorithm calculations applied in this study.